The Seismic Electromagnetic Emissions During the 2010 Mw 7.8 Northern Sumatra Earthquake Revealed by DEMETER Satellite - Zhima, Zeren; Hu, Yunpeng; Piersanti, Mirko; Shen, Xuhui; De Santis, Angelo; Yan, Rui; Yang, YanYan; Zhao, Shufan; Zhang, Zhenxia; Wang, Qiao; Huang, Jianping; Guo, Feng (Frontiers in Earth Science, 2020)
The abnormal electromagnetic emissions recorded by the DEMETER satellite associated with the April 6, 2010 Mw 7.8 northern Sumatra earthquake are examined in this study. The variations of wave intensities recorded by revisiting orbits from August 2009 to May 2010 indicate that some abnormal enhancements at ELF (Extremely Low Frequency) range of 300 - 800 Hz occurred from 10 to 3 days before the main shock, while they remained a relatively smooth trend during quiet seismic activity times. The perturbation amplitudes relative to the background map which were built by using the same-time seasonal window (February 1 to April 30) data from 2008 to 2010 further suggested strong enhancements of wave intensities during the period prior to the earthquake. We computed the wave propagation parameters for the electromagnetic field waveform data by using the Singular Value Decomposition method, and results show that there are certain portions of the ELF emissions obliquely propagating upward from the Earth towards outer space direction at 10 and 6 days before the main shock. The potential energy variation of acoustic-gravity wave (AGW) suggests the possible existence of AGW stability with wavelengths roughly varying from 5.45 to 9.49 km in atmosphere at the time of the main shock. In this study, we comprehensively investigate the link between the electromagnetic emissions and the earthquake activity through a convincing observational analysis, and preliminarily explore the seismic-ionospheric disturbance coupling mechanism, which is still not fully understood at present by the scientific community.